2021
DOI: 10.1371/journal.pone.0250954
|View full text |Cite
|
Sign up to set email alerts
|

Marine endophytic fungi associated with Halopteris scoparia (Linnaeus) Sauvageau as producers of bioactive secondary metabolites with potential dermocosmetic application

Abstract: Marine fungi and, particularly, endophytic species have been recognised as one of the most prolific sources of structurally new and diverse bioactive secondary metabolites with multiple biotechnological applications. Despite the increasing number of bioprospecting studies, very few have already evaluated the cosmeceutical potential of marine fungal compounds. Thus, this study focused on a frequent seaweed in the Portuguese coast, Halopteris scoparia, to identify the endophytic marine fungi associated with this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 119 publications
(199 reference statements)
1
5
0
Order By: Relevance
“…Two Nigrospora species, N. oryzae and N. sphaerica , are frequently encountered. Nigrospora oryzae has been consistently reported from macroalgae [ 16 , 43 ] and was also commonly detected in this study on three islands and on three types of algae. However, Nigrospora sphaerica was not detected on marine macroalgae in this study, although it has been commonly reported in various marine environments [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 76%
“…Two Nigrospora species, N. oryzae and N. sphaerica , are frequently encountered. Nigrospora oryzae has been consistently reported from macroalgae [ 16 , 43 ] and was also commonly detected in this study on three islands and on three types of algae. However, Nigrospora sphaerica was not detected on marine macroalgae in this study, although it has been commonly reported in various marine environments [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 76%
“…The solid media extract of Aspergillus chevalieri (F2-SF), showed higher antioxidant potential, as compared to the two other isolates. The seaweed endophyte A. chevalieri , obtained by Calado et al [ [52] , [60] ], also showed the highest antioxidant ability among all the tested extracts. It showed EC 50 of 35.5 μg/ml in the DPPH scavenging assay, TPC 402.9 ± 42.0 mg GA/g and FRAP 3256.1 ± 174.3 μM FeSO 4 /g.…”
Section: Discussionmentioning
confidence: 85%
“…Endophytic fungi are a diverse group, inhabiting and degrading terrestrial ( Arnold, 2007 ; Kusari et al, 2012 ; Rana et al, 2019 ; Yan et al, 2019 ; Manganyi and Ateba, 2020 ) and marine vegetation ( Hamzah et al, 2018 ; Noorjahan et al, 2019 ; Teixeira et al, 2019 ; Parthasarathy et al, 2020 ; Calado et al, 2021 ), linking ecology to plant pathology ( Shipunov et al, 2008 ; Behie and Bidochka, 2014 ; Leach et al, 2017 ; Latz et al, 2018 ; Poveda et al, 2020 ), and evolution ( Miyauchi et al, 2020 ; Tiwari and Bae, 2020 ), as well as plant communication and nutrient distribution ( Kothe and Turnau, 2018 ; Sharifi and Ryu, 2021 ). Endophytic fungi live in symbiosis within the macroalgae, as in terrestrial vegetation ( Jia et al, 2016 ), or in marine vegetation ( Hamzah et al, 2018 ; Noorjahan et al, 2019 ; Calado et al, 2021 ) and are likely to regulate many biochemical pathways through their life cycle ( Navarro-Meléndez and Heil, 2014 ; Latz et al, 2018 ). Clearly, endophytic fungi are likely of considerable importance, potentially for OM degradation (macrophytes, or other vegetation sources) and C cycling in terrestrial and marine environments.…”
Section: Discussionmentioning
confidence: 99%